Performance characteristics of Paralympic swimming - Fulton, S. K. (University of the Sunshine Coast, 2008)
Margins of victory in elite swimming competitions are often small and are influenced by the performance characteristics of the athlete. The Paralympic Games is the highest level of competition for elite swimmers with a disability. The key performance characteristics of these athletes depend on training and technique, yet these have not been wholly quantified and documented. The purpose of this thesis was to enhance training and optimise competition outcomes for Paralympic swimmers by examining variability and progression in competition times, training characteristics, and the contribution of kicking to performance. The variability and progression of performance from competition to competition provides guidelines for the global improvements required for swimmers to succeed. To achieve this objective, the training programs used to prepare swimmers for competition must be effective. Kicking training is a key component of the training process prescribed by coaches however there is no simple method to measure the kinematics of the kick. Quantifying the patterns of kick count and kick rate was achieved by using inertial sensor technology. When net propulsive force of the kick is measured at race velocities and using different kicking amplitudes, coaches and sport scientists were able to identify key technical and training characteristics to increase kicking velocity. Study one examined the magnitude of variability and progression in competitive performance in the 100 m freestyle event for elite swimmers with a disability. The major results of this study found that annual improvements in competitive performance of 1-2%, which account for variability (~1.3%), progression (~0.5%) and the level of a competition (~1.5%), are required for top-ranked Paralympic swimmers to substantially increase medal prospects. Improvements of this magnitude require an effective training program. In study two, training volume and intensity (load) were quantified for 16 Paralympic swimmers, in the 16 weeks prior to a World Championship to determine the weekly pattern of training load throughout a training block. Increases in main-set training volume (~24, ±19%: mean, ±90% confidence limits) and perceived exertion (~7, ±3%) were observed mid-season prior to substantial reductions in volume (~24, ±18%) and maintenance of intensity during the taper. There was no clear association (correlation coefficient) between training volume and functional ability of the swimmers, or between training measures and performance. Kick sets were prescribed in the majority of the training sessions in study two though lap time was the only quantifiable variable. The characteristics of a swimmer`s kick are unknown. The kick is partially obscured by turbulence and therefore difficult to measure. The aim of study three was to evaluate the application of inertial sensor technology, when attached to the legs, to quantify kick count and kick rate in freestyle swimming. The validity and reliability of this new method of quantifying kicking measures were evaluated. Kicking patterns were then measured in study four for 14 Paralympic swimmers in 100 m freestyle swimming time trials to determine changes and differences within and between a) swimming and kicking-only trials; b) Paralympic classes and disabilities; and c) 100 m distances. Kick count did not change within a trial, though substantial decreases in kick rate (~12, ±1%) were observed by the 3rd 25 m segment. The relationship between swimming and kicking-only kick rates in study four was substantial; r = 0.67 (0.55 to 0.76). Some swimmers have a better transfer of kick rate from kicking-only to swimming than others. Study five examined the influence of kicking velocity and amplitude on net force and kick rate in 12 Paralympic swimmers using a dynamometer and force platform system. The net force naturally increased with a faster tow velocity (~24, ±5%), without a concomitant increase in kick rate that remained largely unchanged at ~150 kicks·min-1 for all velocities. Deep amplitude kicking substantiay decreased kick rate (~14, ±5%) and increased force (~10, ±5N). This relationship between kick rate, velocity, amplitude and net force provides insight into guidelines for the prescription of kick training. The key for Paralympic swimmers is to implement kick rates and amplitudes, complementary to the arm stroke, that elicit faster swimming velocities with a relative decrease in net towing force. In conclusion, the results of this series of studies suggest that coaches and swimmers should address issues of variability and progression in competition times. These estimates can be used to set realistic performance goals when planning for major competitions and yearly training programs. Coaches, when planning the yearly training season for Paralympic swimmers, should follow similar periodised patterns to Olympic swimmers. Contemporary training facilitates substantial improvements in freestyle velocity when kick rate is increased and kick amplitude is maintained. Integration of these key characteristics should enhance Paralympic swimming performance and increase chances of success in competition.